Innovation of Learning Device and Learning Media of Web-Based Nias Dance Techniques in Students of Dance Education Program of Art and Language Faculty in State University Of Medan (UNIMED) - Rahayu, Tuti; Rahmah, Sitti (Budapest International Research and Critics University, 2019)
Nias Dance Technique is one of the subjects included in the Presentation group, but the learning belongs to the education group. The aim is to innovate learning tools and web-based instructional media on Nias dance technique for students of Dance Program of Art and Language Faculty in State University of Medan. The type of research used is research and development (R&D). R&D is a research method used to produce certain products, and test the effectiveness of these products. The results of this study are that the Learning Tools and instructional media are to facilitate students in learning Nias Dance through web schology in the Department of Sendratasik. Learning device innovation consists of KKNI curriculum starting from RPS, LK, Assessment Rubric, Teaching Materials, VCD with dance material No Tatema Mbola.